Penggunaan Dana Desa Dalam Mewujudkan Pemenuhan Hak Masyarakat Atas Air Bersih di Desa Oelnaineno Kecamatan Takari Kabupaten Kupang - Imanuel Nenobahan; Yohanes G. Tuba Helan; Hermanwati Agatha Y. Dai (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Clean water is a basic need that is also the right of every citizen, especially related to social and economic rights. This shows that the availability of clean water is one of the main needs that must be met, because its role is very important in supporting various community activities in various fields of life. Village funds are funds sourced from the State Revenue and Expenditure Budget (APBN) intended for villages that are transferred through the district/city Regional Expenditure Budget (APBD) which is used to finance the implementation of government, implementation and development, community development and community empowerment. Oelnaineno, Takari District, Kupang Regency. This research is empirical research, namely with data in the field as the main source of data such as interviews and observations. Based on the results of the research that has been carried out, it is obtained that: (1) The management of village funds by the Oelnaineno village government in meeting the community's needs for clean water has been carried out in accordance with procedures and gradually, this is marked by the creation of mini reservoirs and reservoirs in each hamlet. (2) Factors that affect the Oelnaineno village government in allocating village funds to fulfill the rights of the people of Oelnaineno village to clean water are: (a) Legal factors, namely the absence of village regulations, in the Perkades the rules related to clean water are still broadly defined. (b) Law enforcement factors, the Oelnaineno village government does not provide socialization related to clean water on a regular basis. (c) The factor of facilities or facilities is the very lack of spring water sources in Oelnaineno village, the water reservoirs made by the village government are still few so that people have to queue when taking water, there is no drilled well as a source of clean water that can survive during the dry season. (d) Community factors that are less active in helping the village government at the planning stage to the implementation of clean water handling in Oelnaineno village